How does emotional exhaustion among Chinese college students affect mental health? A mixed-methods study in Zhejiang, China - Jiang, Longyuan; Fang, Lefei; Xu, Yuanqi; Zhang, Qinyu; Dai, Shujing; Tian, Jiakun; Wu, Wei; Fang, Yuan; Zhang, Meili; Yu, Haiyan (Frontiers in Public Health, 2025)
IntroductionThis study is based on the social ecology theory and clarifies how emotional exhaustion acts as a proximal mechanism to transmit macro cultural norms, meso institutions and need systems, and micro cognition and behavioral processes to the mental health of college students.MethodsWe conducted a questionnaire survey in 26 universities in Zhejiang Province and received valid responses from 600 students. We used the covariance structural equation model to estimate direct effects and mediating effects, and used fuzzy set qualitative comparative analysis to identify asymmetric configurations sufficient to lead to high-risk outcomes.ResultsThe structural equation model showed that the culture of internal competition, academic pressure, employment pressure, rumination thinking, and negative personal behaviors significantly increased emotional exhaustion, while the laid-back culture and relationship needs were not significant. Emotional exhaustion significantly predicted poorer mental health and played a mediating role between each predictor and the outcome. The fuzzy set qualitative comparative analysis identified three types of paths.DiscussionThe results collectively indicate that emotional exhaustion is a transmission hub in the social ecosystem. The evidence of symmetric mean effects and asymmetric configurations mutually corroborates, suggesting the necessity of multi-level intervention and hierarchical implementation.